Pengaruh Kepercayaan Diri Terhadap Hasil Belajar Siswa pada Mata Pelajaran Matematika Kelas V SDN Dukuh - Uswatun Hasanah; Agus Priyatno; Willis Firmansyah (Fakultas Agama Islam dan Pendidikan Guru, 2022)
This research is motivated by the weak self-confidence of students in the learning process in class. Basedon observations on Mathematics subjects the teacher does notuse interesting learning media. The purpose of this study was todetermine the effect of self-confidence on student learningoutcomes in the fifth grade of SDN Hamlet in Mathematics. Themethod used is functional correlation using regression analysisby collecting data through a questionnaire, data presented inthe form of numbers and values. It can be concluded that thereis an effect of self-confidence on the mathematics learningoutcomes of Dukuh Elementary School students. This can beproven by obtaining the value of count> table (6.156> 1.734), sothat H0 is rejected, which means that confidence affects thelearning outcomes.